Glycan-based scaffolds and nanoparticles as drug delivery system in cancer therapy - Qin, Henan; Teng, Yibin; Dai, Rui; Wang, Aman; Liu, Jiwei (Frontiers in Immunology, 2024)
Glycan-based scaffolds are unique in their high specificity, versatility, low immunogenicity, and ability to mimic natural carbohydrates, making them attractive candidates for use in cancer treatment. These scaffolds are made up of glycans, which are biopolymers with well biocompatibility in the human body that can be used for drug delivery. The versatility of glycan-based scaffolds allows for the modulation of drug activity and targeted delivery to specific cells or tissues, which increases the potency of drugs and reduces side effects. Despite their promise, there are still technical challenges in the design and production of glycan-based scaffolds, as well as limitations in their therapeutic efficacy and specificity.